Religion and Public Health during the Time of COVID-19 - Flescher, Andrew; Zimbelman, Joel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection of essays addresses a range of topics probing the interface between religious practice and the COVID-19 pandemic. Significant attention is given to religious and cultural debates over health care policy as well as vaccination policy development in the United States, but contributions from Africa, Asia, South America, and Europe are included as well. In addition to the North American perspectives (with an emphasis on the white evangelical Christian encounter with public health regulation), the volume highlights voices from Islamic Nigeria and southern Africa, traditional Confucian culture, Greek Orthodoxy, Catholic social teaching, as well as the insights of Haṭha yoga from the Hindu tradition.